Etude De La Vulnerabilite Aux Risques D’inondations Dans La Ville De Meknes. Apport Des Sig, Du Mnt Et Des Modeles Empiriques - Rhazi, Abdelaziz; Essahlaoui, Ali; El Hmaidi, Abdellah; El Ouali, Abdelhadi (European Scientific Journal, ESJ, 2017)
The present study aims to assess, identify and map the risk of flooding urban in the aim of protecting the city of Meknes (center of northern Morocco) from the flooding of the Oued Boufekrane which runs along the city from the south to the north. It is carried out using the tools modeling, of empirical formulae and functions integrated into the software dedicated to the systems of Geographic Information System (GIS) and by exploiting the climate data, hydrological, topographical, geological, etc. The slopes of the watershed of the Oued Boufekrane vary approximately between 1 and 19%. They allow determining the areas and neighborhoods vulnerable to the risk of flooding with slopes not exceeding the 6%. The vulnerability to the risk of flooding which requires a priority intervention affects mainly the neighborhoods located in the southwest of the agglomeration of Meknes and along the valley of the Oued Boufekrane.